Kemampuan berpikir kreatif matematis siswa smp melalui soal open ended - Buyung, Buyung (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
Creative thinking skills are an important skill that must be owned by students, but most students still have low creative thinking skills. This research aims to describe students' mathematical creative thinking skills through open ended problems. The data collection technique used in this study is to provide mathematical creative thinking skills using open ended questions in students of 8th grade torsina 3 Singkawang as many as 2 problems. The data analysis techniques used in this study are data reduction, data presentation, and conclusion withdrawal. The result of this study is the mathematical creative thinking ability of some students who work on open ended problems have fulfilled the components of profitability and flexibility for problem number 1 but there are also those who do not meet all components. And for problem number 2 most students do not meet all three components of mathematical creative thinking skills. So it can be concluded that the mathematical creative thinking skills of junior high school students who work on open ended problems are in the low category.